2014
DOI: 10.1111/evj.12282
|View full text |Cite
|
Sign up to set email alerts
|

A topographic anatomical study of the equine epiploic foramen and comparison with laparoscopic visualisation

Abstract: Several clinically relevant structures delineate the epiploic foramen. Its defining structure consists, in part, of elastin fibres. Anatomical and laparoscopic knowledge may assist surgeons in developing interventions to treat diseases involving the epiploic foramen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 7 publications
3
29
0
1
Order By: Relevance
“…Introduction of the diabolo-shaped mesh construct in the horses that were recovered from anaesthesia and had comparable EF dimensions was uneventful and resulted in complete closure of the EF with dense fibrous tissue after 1 month. In a previous anatomical study, the mean circumference of the EF in 30 normal horses was 11.6 AE 2.6 cm [14] which is comparable to the estimated median circumference of the EF of 11 cm in the pilot study and 12 cm in the main study of the present investigation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Introduction of the diabolo-shaped mesh construct in the horses that were recovered from anaesthesia and had comparable EF dimensions was uneventful and resulted in complete closure of the EF with dense fibrous tissue after 1 month. In a previous anatomical study, the mean circumference of the EF in 30 normal horses was 11.6 AE 2.6 cm [14] which is comparable to the estimated median circumference of the EF of 11 cm in the pilot study and 12 cm in the main study of the present investigation.…”
Section: Discussionsupporting
confidence: 86%
“…The estimated median dimension of the EF was 3 (2-4) fingers corresponding to a median circumference of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16) cm measured on the fingers of a 7.5 gloved surgeon.…”
Section: Main Studymentioning
confidence: 99%
“…Subsequently the protected trocar was replaced by a 58 cm 30° laparoscope (Karl Storz GmbH, Tuttlingen, Germany). The region of the epiploic foramen was thoroughly inspected as described previously . Any changes in anatomy, inflammation, presence of scar tissue, or spontaneous closure of the epiploic foramen were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The omental vestibule is funnel shaped with 2 openings, a smaller one on the right side of the median plane, which is the epiploic foramen, and a larger one on the left side, which is the opening from the omental vestibule to the caudal recess of the omental bursa . It has been suggested that the funnel‐like configuration could be the reason for the predominant left‐to‐right epiploic foramen entrapment occurrence . Increased intra‐abdominal pressure during cribbing could be the reason for herniation through this structure in horses that crib …”
mentioning
confidence: 99%
“…Vet. Zootec., v.70, n.6, p.1685-1690, 2018 por estruturas nobres, como pâncreas, fígado, veias porta e cava caudal, estômago e duodeno (Freeman e Pearn, 2015;Bergen et al, 2015). O forame epiploico comunica a bursa omental com a cavidade peritoneal (Vachon e Fischer, 1995;Schmid, 1997;Mueller et al, 2008;Freeman, 2012;Freeman e Pearn, 2015).…”
Section: Introdução unclassified